2018
DOI: 10.21037/jtd.2018.03.165
|View full text |Cite
|
Sign up to set email alerts
|

Status of coexisting chronic obstructive pulmonary disease and its clinicopathological features in patients undergoing lung cancer surgery: a cross-sectional study of 3,006 cases

Abstract: COPD is a common comorbidity of early stage lung cancer. Lung cancer patients with coexistence of COPD have obviously different clinicopathological features compared to patients without COPD, which requires special attention and management during the perioperative period of lung cancer.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Over the past decade, increasing studies have reported that many blood routine examination‐derived biomarkers, such as NLR, PLR, and LMR, whose levels could be closely related to systemic inflammation and immune response status . These biomarkers are proved to be well associated with various infectious diseases, oncological diseases and autoimmune diseases . In recent years, following NLR, PLR, and LMR, SII has been discovered as an emerging indicator for these diseases and shed great predictive and diagnostic potential .…”
Section: Discussionmentioning
confidence: 99%
“…Over the past decade, increasing studies have reported that many blood routine examination‐derived biomarkers, such as NLR, PLR, and LMR, whose levels could be closely related to systemic inflammation and immune response status . These biomarkers are proved to be well associated with various infectious diseases, oncological diseases and autoimmune diseases . In recent years, following NLR, PLR, and LMR, SII has been discovered as an emerging indicator for these diseases and shed great predictive and diagnostic potential .…”
Section: Discussionmentioning
confidence: 99%
“…COPD is a common respiratory disease which is featured by progressive lung function decline and persistent airflow obstruction [26]. It should be noted that lung cancer patients undergoing surgery would sometimes have COPD as a comorbidity, which significantly impacts lung cancer perioperative management [27,28]. In this study, compared to RV/TLC ≥ 45% (another indictor which may also reflect patients existing obstructive ventilation dysfunction), COPD, namely FEV 1 /FVC < 70%, appeared to be inferior in predicting prolonged p-LOS.…”
Section: Discussionmentioning
confidence: 99%
“…With the recent progress in imaging technology and the popularization of low-dose spiral computed tomography, an increasing number of patients have been clinically identified with pulmonary nodules, some of which have been identified as early non-small cell lung cancer after surgery ( 1 , 2 ). However, some patients develop acute or chronic cough symptoms after lung surgery, with a deleterious effect on their quality of life ( 3 - 5 ).…”
Section: Introductionmentioning
confidence: 99%